Use of fuzzy knowledge base of mamdanizadeh for spatial interpolation of population density - Дубовой, Володимир Михайлович; Сольський, Олександр Сергійович (Eastern-European Journal of Enterprise Technologies, 2013)
For early detection of pests (plant diseases) in the fields of agricultural enterprise and taking the appropriate measures on plant protection, it is necessary to conduct constant phytosanitary monitoring, which requires specific knowledge and resources, which may be inaccessible. The propagation of pests is influenced by many factors, most of which are not formalized, or mathematical description is very difficult, information about these factors may be fuzzy or incomplete. In such conditions, the results of interpolation are also fuzzy in nature. This paper proposes the solution to the problem of spatial interpolation of the number of pests using the fuzzy-set theory and fuzzy logic. The proposed geoinformational model is based on the fuzzy knowledge base of Mamdani-Zadeh. The developed model is one of the main IT models in plant protection